Restarted GMRES preconditioned by deflation - Erhel, Jocelyne; Burrage, Kevin; Pohl, Bert (Journal of computational and applied mathematics, 1996)
This paper presents a new preconditioning technique for the restarted GMRES algorithm. It is based on an invariant subspace approximation which is updated at each cycle. Numerical examples show that this deflation technique gives a more robust scheme than the restarted algorithm, at a low cost of operations and memory.